2015
DOI: 10.1194/jlr.m054288
|View full text |Cite
|
Sign up to set email alerts
|

Atomistic MD simulation reveals the mechanism by which CETP penetrates into HDL enabling lipid transfer from HDL to CETP

Abstract: This article is available online at http://www.jlr.org the atheroprotective functions of HDL ( 1 ) have been driving forces for research on HDL as a potential therapeutic target ( 2 ). Several therapies aimed at increasing HDL-C levels have been tested. Among them is the inhibition of cholesterol ester transfer protein (CETP) ( 2, 3 ), a plasma neutral lipid transfer protein that mediates exchange/ transfer of neutral lipids between HDL and apoB-100-containing lipoproteins and is involved in the reverse choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 37 publications
7
45
0
Order By: Relevance
“…As a result, the N-terminal distal domain of CETP has less binding affinity to the flat surface lipid plane of polyhedral VLDLs than to the curved surface of spherical HDL. This hypothesis is consistent with the hydrophobic distal end of the N-terminal β-barrel domain of CETP interacting with HDL surface lipids and initializing CE uptake from the HDL core, as suggested by molecular dynamics simulations ( 21 , 44 , 51 ). It is also consistent with the observation that most CETPs in plasma bind to HDLs instead of VLDLs, which is due to the lower surface curvature (less hydrophobicity) of VLDLs, although the surface lipids of VLDLs are the same as those of HDLs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…As a result, the N-terminal distal domain of CETP has less binding affinity to the flat surface lipid plane of polyhedral VLDLs than to the curved surface of spherical HDL. This hypothesis is consistent with the hydrophobic distal end of the N-terminal β-barrel domain of CETP interacting with HDL surface lipids and initializing CE uptake from the HDL core, as suggested by molecular dynamics simulations ( 21 , 44 , 51 ). It is also consistent with the observation that most CETPs in plasma bind to HDLs instead of VLDLs, which is due to the lower surface curvature (less hydrophobicity) of VLDLs, although the surface lipids of VLDLs are the same as those of HDLs.…”
Section: Discussionsupporting
confidence: 86%
“…Because the N-terminal β-barrel domain of CETP facilities the hydrophobic interactions with surface lipids for initializing CE uptake ( 21 , 44 , 51 ), we predicted the LDL surface could have more binding affinity to the N-terminal β-barrel domain of CETP that is between its binding affinities for HDL and VLDL because of the partially flat surface and partially curved surface revealed by the cryo-EM studies ( 25 , 52 55 ). The intermediate level of binding affinities between HDL and VLDL may explain how CETP can transfer CE from HDL to LDL and from LDL to VLDL.…”
Section: Discussionmentioning
confidence: 99%
“… 26 Several reports on CETP inhibitors have suggested a putative mechanism for CETP inhibition on the basis of competitive interactions with CETP and HDL. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%
“…Recent electron microscopy (EM) studies have shown the presence of a ternary complex among CETP, HDL, and LDL/VLDL ( 16 ) in which the CETP N-terminal distal end interacts with HDL via a hydrophobic interaction ( 17 ). Independently, molecular dynamics (MD) simulations have revealed that the CETP distal ends are structurally flexible ( 18 ), and the N-terminal end penetrates into the HDL surface and takes up a CE molecule ( 19 ). A tunnel mechanism has been proposed because the CETP crystal structure displays a long hydrophobic central cavity containing two CE molecules ( 16 ).…”
Section: Introductionmentioning
confidence: 99%